How Crises Shaped Economic Ideas and Policies: Wiser After the Events? - Christodoulakis, Nicos (Springer, 2015)
This book explores how successful the various tenets of economic thought have been in prognosticating or remedying economic crises. Examining key episodes in economic history, from famines in antiquity to present-day financial collapse, the author finds that several theories failed to cope with a crisis and lost their academic impact. The author also presents cases in which major theoretical innovations were achieved after the experience of a crisis as well as cases where a completely new theory was needed to explain and face the events. This book will appeal to researchers and scholars interested in understanding how theoretical developments in economics are affected by real-world economic crises.